Advice Methods And Sayings In The Educational Perspective Of The Quran - Supriatna Mubarok; Mariya Ulfah; Tuti Nursafitri; Mastuhi Mastuhi (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this research is to analyze the methods of advice and proverbs contained in Q.S. Yusuf, verse 111. This research is in the nature of library research, that is, research whose primary object is literature or library materials related to the problems studied from various literatures.This article applies the descriptive analysis method. The results of the research show that the story method can be taken from the story of Yusuf and also from other prophets. From this story, an